"We want change", but who's we? How to transition cultural change in the digital era as a team. Issue 5 (14th October 2019) - Berges, Rafael Pablo; Kon, Fabian
Abstract : Purpose: The new digital world and the big corporations who have been around for more than 80, 100 or more years tend to be perceived as incompatible. This study aims to highlight how the key to a digital mindset is not the size of the company or the company's track record, but an evolving organizational culture. This case outlines the strategy, tools and techniques to make cultural change and digital transformation possible. Design/methodology/approach: The authors synthesize their organization's ongoing transformation in the past two years, engaging every person at Galicia, from top management to all 6, 000+ employees through workshops, especially designed meetings and internal communications campaigns to align the company's goals and move forward together. Findings: This case study pinpoints the key aspects that should be looked after when working on organizational culture and the main players and/or concepts that organizations should count on as allies for change. Originality/value: This case provides concrete methods and good practices to create cultural change and employee engagement, regardless of the scale of the company, through first-hand learnings that can be applied in any organization.